Visual Inspection Test with Acetic Acid for Cervical Cancer Screening: Willingness and Acceptability among Reproductive Age and Married Women - Rozaliamisah Binti Hassan; Edwin Armawan; Insi Farisa Desy Arya (Faculty of Medicine Universitas Padjadjaran, 2018)
Background: Cervical cancer is a preventable disease, thus early screening test should be performed for early cervical cancer prevention. Previous studies showed that among all of the screening techniques, visual inspection with acetic acid is an alternative, simple safe cervical cancer prevention technique. This study aimed to identify the willingness and acceptability of visual inspection with acetic acid among reproductive age and married women as cervical cancer prevention.Methods: A descriptive cross-sectional study was conducted among 100 reproductive age and married women in Jatinangor subdistrict West Java in 2014. A validated questionnaire was used to obtain information about the respondents’s characteristics, risk factors of cervical cancer, willingness and acceptability of Visual Inspection using Acetic Acid Test (VIA). The collected data were presented using tables.Results: Out of 100 respondents, 93% ever heard of cervical cancer, however 79% were aware of cervical cancer. As high as 96% were aware of the importance of cervical cancer screening, however 36% were aware of cervical cancer screening, and 19% were aware of VIA test. While 83% never had previous education on cervical cancer, 91% reported willingness to take part on cervical cancer education and 83% willingness of cervical cancer screening. Noted 17% were non-acceptance of VIA test for future cervical cancer screening due to their busy life and afraid of the outcome result.Conclusions: The majority of reproductive age and married women are willing and accept VIA test for cervical cancer screening.